A comparison of silica and porous graphitic carbon as support materials for a chiral selector in HPLC - Oxelbark, Joakim; Claeson, Sofia (Tetrahedron: asymmetry, 2002)
The tartaramide based chiral selector 2 was synthesized, coated onto porous graphitic carbon (PGC), and evaluated as a chiral stationary phase for HPLC. Its performance was compared to the silica based sorbent 1, containing the same chiral moiety. The retention and separation characteristics of the two columns were found to be correlated, but separation factors and column efficiencies were constantly lower on the PGC column. Coating of PGC as a novel and simple means to evaluate chiral selectors was evaluated. Graphic